Call for Decision Support for High-Alert Medication Administration Among Pediatric Nurses: Findings From a Large, Multicenter, Cross-Sectional Survey in China - He, Mengxue; Huang, Qin; Lu, Hong; Gu, Ying; Hu, Yan; Zhang, Xiaobo (Frontiers in Pharmacology, 2022)
Background: Children have a higher risk of medication errors (MEs) than adults. High-alert medications (HAMs) is a group of medications that could cause significant patient harm or even death when used in error. Nurses are actively involved in medication administration. This study aimed to estimate the knowledge, decision-making basis and confidence and decision support needs related to HAMs among pediatric nurses in China. Methods: A web-based, cross-sectional survey was conducted among pediatric nurses who were recruited from 14 hospitals using a convenient sampling technique. Data were collected using a self-administered instrument composed of four parts: demographic characteristics of participants, participants’ knowledge about HAMs, participants’ self-evaluation of the basis of and confidence in decision-making, and decision support needs regarding HAMs. The maximum score for HAM knowledge was 100. All data were entered and analyzed using SPSS 20.0. Results: A total of 966 nurses participated in this study. Nurses were found to have insufficient knowledge about HAMs, with a median (IQR) of 75.0 (70.0, 80.0). Knowledge about HAM administration was significantly higher than that about HAM regulation, with a p value <0.001. The three lowest-scoring items concerned HAM regulation, and the “Treat fentanyl skin patches as a regulated narcotic” item obtained the lowest score, with only 1/5 of respondents answering it correctly. Most participants reported that their basis for decision-making about HAMs was drug instructions (90.0%) or drug handbooks (81.9%) and evaluated their confidence in decision-making about HAMs as high or relatively high (84.6%). The decision-making difficulties when encountering HAMs focused on most stages of HAM administration, especially the appropriateness of prescriptions, checks, preparation and administration. The vast majority of participants assessed decision support as necessary or very necessary (92.0%), and the most popular options for decision support were computerized clinical decision support systems (46.4%) and real-time online communication with pharmacists (23.9%). Conclusion: Our study demonstrated the inadequacies in HAM knowledge, the basis and difficulty of decision-making, and decision support needs regarding HAMs in Chinese pediatric nurses. Nurses need greater support in HAM administration, including not only training but also adequate technology, mutually beneficial interprofessional collaboration, and a positive institutional culture.